1987
DOI: 10.1111/j.1348-0421.1987.tb03136.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FLONLIZER®, Ultraviolet Sterilizer, on Legionella Species Inhabiting Cooling Tower Water

Abstract: Legionella pneumophila in sterile distilled water was not detected after ultraviolet irradiation by FLONLIZER®, a new‐type sterilizer, at a flow rate of 82.5 to 364.8 liters/hr. When irradiated by FLONLIZER® at a flow rate of under 324.0 liters/hr, no viable cells of legionellae, other heterotrophic bacteria and bacterivorous protozoa were detected in the cooling tower water, which was found to contain L. pneumophila. No viable cells of L. pneumophila and L. bozemanii suspended in sterile distilled water were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

1988
1988
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…pneumophila has been obtained by U.V. doses of 2.8-6.2 mWs cm-2 (Antopol and Ellner 1979;Yamamoto et al 1987). Thus, in the field experiment reported here, the elimination of legionellas in the radiator was not as efficient as in the laboratory studies mentioned above.…”
Section: Discussioncontrasting
confidence: 57%
“…pneumophila has been obtained by U.V. doses of 2.8-6.2 mWs cm-2 (Antopol and Ellner 1979;Yamamoto et al 1987). Thus, in the field experiment reported here, the elimination of legionellas in the radiator was not as efficient as in the laboratory studies mentioned above.…”
Section: Discussioncontrasting
confidence: 57%
“…There is no residual effect, and chemicals are not added once the water leaves the UV reactor [20]. Yamamoto et al [21] confirmed the killing rate of Legionella, based on a dose of UV light when a UV sterilizer generating a wave length of 254 nm was used. The results of the experiments confirmed that a UV sterilizer could be used to control Legionella in a cooling tower.…”
Section: Introductionmentioning
confidence: 99%
“…Even cooling-tower water contaminated with dirt could be sterilized effectively by a UV sterilizer at an optimum flow rate (10). UV sterilizers tested have set up the optimum flow rate for killing microorganisms in cooling-tower water.…”
mentioning
confidence: 99%